Analysis of static sealing rules of foamed silicone rubber based on a porous media model. Issue 3 (May 2020) - Wen, Tianzheng; Guo, Fei; Huang, Yijie; Zhu, Shixing; Jia, Xiaohong
We established a method for calculating and analyzing the static leakage rate based on a porous media model for foamed silicone rubber materials. The mechanical properties of the foamed silicone rubber material under macroscopic compression were described by the Ogden third (foam) model in the finite-element hyperelastic model. It solved the problem of difficult convergence of large compressible and volume compressible cell materials. The size and distribution of the cells on the surface of the foamed material were obtained by a white-light interferometer and mathematical fitting. The boundary conditions for solving the porous medium model were obtained by the coupling of the macroscopic contact pressure and the microscopic cell contact pressure. For the unique cell structure and contact state of the surface of the foamed material, the flow state of the fluid at the sealing interface was described by a porous medium model, and the leak rate was obtained. In addition, this article analyzed the effect of different compression and the relative pressure of the sealing end face on the leakage.